(untitled) (Journal of Partial Differential Equations, 2025)
The incompressible limit of nonisentropic ideal magnetohydrodynamic equations with general initial data in the whole space R^3 is proved in this paper. The uniform estimates of solutions with respect to the Mach number are obtained by using energy estimate. Strong convergence results of the smooth solutions are established by using Strichartz’s estimates in the whole space.